2022
DOI: 10.21203/rs.3.rs-1443377/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Comparative Study on Forecasting of Long-term Daily Streamflow using ANN, ANFIS, BiLSTM, and CNN-GRU-LSTM

Abstract: One of the essential phases in water resource planning and management is streamflow forecast. It is necessary for the functioning of hydropower plants, agricultural planning, and flood control. The present study applied Artificial Neural Network (ANN) model, Adaptive Neuro-Fuzzy Inference System (ANFIS), Bidirectional LSTM (BiLSTM), and hybrid Convolutional Neural Network (CNN) Gated Recurrent Unit (GRU) Long-Short Term Memory (LSTM) model to predict the long-term daily streamflow in the Colorado River, USA. 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
(2 reference statements)
0
0
0
Order By: Relevance
“…An analysis of the univariate streamflow predictions by Zhang et al [12] found that data-driven models are widely used because of their simplicity and minimal data needs. The most frequently artificial intelligence (AI) models used in streamflow forecasting are neural-based fuzzy inference systems (ANFIS) [13], support vector machines (SVM) [14], and artificial neural networks (ANN) [15]. As a simple operational model, ANN offers significant non-linear mapping capabilities [10].…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the univariate streamflow predictions by Zhang et al [12] found that data-driven models are widely used because of their simplicity and minimal data needs. The most frequently artificial intelligence (AI) models used in streamflow forecasting are neural-based fuzzy inference systems (ANFIS) [13], support vector machines (SVM) [14], and artificial neural networks (ANN) [15]. As a simple operational model, ANN offers significant non-linear mapping capabilities [10].…”
Section: Introductionmentioning
confidence: 99%